Peningkatan Hasil Belajar IPA Energi dan Perubahannya melalui Metode Eksperimen pada Siswa Kelas IV SDK Wesoer - Rinawati Br Perangin Angin (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This research is motivated by the low learning outcomes of students and the lack of student learning outcomes in learning and the use of learning methods that are less influential in improving student learning outcomes in paying attention to the material presented by the teacher. This study aims to determine and describe how efforts to improve the learning outcomes of fourth-grade students at SDK WESOER in the science subject about Energy and its changes by using the Experimental Method. This research is a classroom action research (CAR), the data collection instruments used are observation, interviews, documentation, and tests. This research consists of 2 cycles, each cycle consisting of 1 meeting. Each cycle consists of the planning, observation, implementation, and reflection stages. The results of the study indicate that the use of the experimental method can improve student learning outcomes on the sub-theme of energy and its changes in fourth grade at SDK Wesoer. Before conducting the research, researchers conducted observations. During the learning process, the teacher did not use the experimental method on the material of energy and its changes, so from 25 students only 8 students got a complete score reaching the KKM with a percentage of 32%, and 17 students got an incomplete score not reaching the KKM with a percentage of 68%. After conducting research using the experimental method on energy and its transformations, in Cycle I, 14 students achieved a passing grade and achieved the Minimum Completion Minimum (KKM) with a percentage of 56%, while 11 students received an incomplete grade, failing to achieve the KKM with a percentage of 44%. In Cycle II, the learning outcomes improved further, with 20 students achieving a passing grade with a percentage of 80%, and 5 students receiving an incomplete grade with a percentage of 20%.